New Strategies to Tackle the Combined Biological and Social Context of Preterm Birth - Montoya-Williams, Diana; Salloum, Ramzi G.; Lorch, Scott A. (American Journal of Perinatology, 2019)
Objective Preterm birth rates in the population and associated racial inequities have remained relatively unchanged in the United States despite research aimed at prevention. This is potentially the result of the multifactorial pathophysiologic pathways that result in preterm birth, where biological and social drivers intersect in unique ways for different women. The field of dissemination and implementation (D&I) science may address this issue by promoting the contextually-aware uptake of science into health and health care delivery.Study Design In this paper, we describe how the field of D&I science may afford new perspectives on preterm birth prevention to researchers and tools to design studies that translate clinical trial data into measurable changes at the level of the population. We discuss key examples where the perspectives and tools of D&I science have been used in conjunction with quality improvement methodology to change preterm birth rates in large population studies. We build on these case studies and suggest future D&I science-informed studies that could be explored.Conclusion Incorporating D&I scientific principles into the design of studies to prevent preterm birth may allow future research to better address the varied ways in which social forces comingle with biological risk factors to result in preterm birth.
Keywords: dissemination science; implementation science; population health; prematurity; social determinants